2, 6‐Bis(diazaboryl)pyridine – A Ligand with Hemilabile Donor and Lewis Acid Functionalities. Issue 4 (22nd January 2020) - Schröder, Jan; Böttcher, Tobias
Abstract: Invited for the cover of this issue is the group of Tobias Böttcher from Universität Freiburg, Germany. The cover image shows the similarity of the chemistry presented to a game of Tetris. Abstract : We think that the system dab 2 py/GaCl 3 is a very convenient entry point for the synthesis of cationic complexes … Read more about the story behind the cover in the Cover Profile and about the research itself in the Full Paper by J. Schröder and T. Böttcher